An Application of the Bootstrap Method to the Analysis of Squared, Standardized Market Model Prediction Errors - Marais, M. Laurentius (Journal of Accounting Research, 1984)
M. Laurentius Marais, An Application of the Bootstrap Method to the Analysis of Squared, Standardized Market Model Prediction Errors, Journal of Accounting Research, Vol. 22, Studies on Current Econometric Issues in Accounting Research (1984), pp. 34-54